Analisis Kemampuan Literasi Matematika Mahasiswa Dalam Menyelesaikan Soal UAS Mata Kuliah Matematika Sekolah SMA/ SMK - Sudrajat, Sudrajat (Galois: Jurnal Penelitian Pendidikan Matematika, 2025)
Mathematical literacy is an essential competency for students in the Mathematics Education study program, particularly in understanding and solving mathematics problems at the high school/vocational school level. Mathematical literacy encompasses not only the ability to perform calculations, but also the ability to formulate, apply, and interpret mathematical concepts in the context of real problems. This study aims to describe students' mathematical literacy skills in solving Final Semester Exam (UAS) questions for the Mathematics course in high school/vocational school. The type of research used is descriptive with a qualitative approach. The study population was fifth-semester Mathematics Education study program students, with three subjects representing high, medium, and low ability levels, selected by random sampling and having taken the UAS for the related course. The research instruments included test questions and interview guidelines, while data collection techniques included test results, interviews, and documentation. Data analysis was carried out through triangulation with three stages: reduction, presentation, and drawing conclusions. The results showed that the average mathematical literacy ability of students was at a moderate level (average score of 67). High-ability students mastered the aspects of formulate, employ, and interpret, medium-ability students only mastered employ and interpret, while low-ability students had not mastered all three aspects adequately. This finding emphasizes the need for learning strategies that focus more on strengthening the formulating aspect, so that all students are able to understand, formulate, and interpret mathematical concepts comprehensively.